2009
DOI: 10.1080/15433710802633247
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of HIV Diagnosis-Related vs. Non-Diagnosis Related Trauma on PTSD, Depression, Medication Adherence, and HIV Disease Markers

Abstract: The present study examined differences in three groups of people living with HIV (PLWH); those who did not meet post-traumatic stress disorder (PTSD) criteria, those with HIV-related PTSD, and those with non-HIV-related PTSD. Patients with PTSD reported more PTSD and depression symptoms and lower levels of medication adherence. Participants with HIV-related PTSD were more likely to report reliving the trauma and were more adherent to HIV medications than participants with non-HIV-related PTSD. Results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 30 publications
0
30
1
Order By: Relevance
“…While HIV-positive persons are exposed to significantly higher rates of trauma than the population in general (Kalichman et al, 2002), being diagnosed and living with HIV can also be a highly stressful and stigmatizing experience (Boarts, Buckley-Fischer, Armelie, Bogart, & Delahanty, 2009). HIV-related stigma may reduce the likelihood that an individual would disclose his or her HIV status, and could thereby negatively impact acquisition of social support and subsequent PTG.…”
Section: Hiv Stigma and Disclosurementioning
confidence: 99%
“…While HIV-positive persons are exposed to significantly higher rates of trauma than the population in general (Kalichman et al, 2002), being diagnosed and living with HIV can also be a highly stressful and stigmatizing experience (Boarts, Buckley-Fischer, Armelie, Bogart, & Delahanty, 2009). HIV-related stigma may reduce the likelihood that an individual would disclose his or her HIV status, and could thereby negatively impact acquisition of social support and subsequent PTG.…”
Section: Hiv Stigma and Disclosurementioning
confidence: 99%
“…inconsistent condom use) and may contribute to increased HIV transmission [3][5]. Second, HIV-positive diagnosis is a stressor that has been found to increase significantly the chance of depression and anxiety [6], [7]. In turn, several studies have suggested that depressive and anxiety disorders may worsen HIV-related health outcomes, and antiretroviral treatment (ART) outcomes in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is associated with inconsistent condom use that may contribute to increased HIV transmission in both low resource and high resource settings [9], [10], [11]. Having a diagnosis of HIV has been found to worsen depression in North America and Europe [12], [13]. In turn, depression worsens HIV-related health outcomes.…”
Section: Introductionmentioning
confidence: 99%